Zespół Goldmanna–Favre’a – opis przypadku - Brydak-Godowska, Joanna; Makowiec-Tabernacka, Marta (Klinika Oczna / Acta Ophthalmologica Polonica, 2009)
Goldmann–Favre syndrome is a very rare vitreoretinal degeneration with typical changes (like retinoschisis, bone corpuscle like pigmentations, dendritic vessels of peripheral retina). We presented a case of Goldmann–Favre vitreoretinal degeneration in 53 years old man, which is observed in our department due to macular changes in the left eye.